Penguatan Literasi Kekerasan dan Perdamaian pada Pengurus Organisasi Santri Pesantren Ulumuddin, Kota Lhokseumawe - Suadi Suadi; Iromi Ilham; Ibrahim Chalid; Rizki Yunanda; Awaludin Arifin; Kurniadi Kurniadi; Rauzana Hilda (Universitas Teuku Umar, 2024)
Pesantren (Islamic boarding school) is one of Indonesia's formal educational institutions with a boarding system. The full-day learning process at Pesantren carries the potential for both physical and verbal violence. The team of the Community Service (PkM) initiated an activity with the theme ‘Strengthening Violence and Peace Literacy for the Santri Organisation Management in Lhokseumawe City.’ This activity aims to optimize violence and peace literacy among Islamic boarding school students. Some agendas are: 1) technical guidance on strengthening literacy; 2) implementation of interactive reading activities; and 3) the formation of discussion groups to examine issues of violence and peace. Ulumuddin Islamic Boarding School, Lhokseumawe, carried out this activity. The activity results showed an increase in the understanding of the santri regarding violence and peace literacy because the material presented included an introduction to the concept of violence, how to resolve conflicts peacefully, and the importance of building peace. Previously, damaging behavior in the form of violence was considered normal by some students. This will have an impact on the normalization of violence in the classroom environment. Providing problem-solving practices through peaceful means helps students understand the mechanism for resolving simple cases among themselves. The hope is that the santri will become effective agents of peace in the pesantren and society.